What drives inhaler prescription for asthma patients? Results from a real-life retrospective analysis. (May 2020) - Lavorini, F.; Bianco, A.; Blasi, F.; Braido, F.; Corsico, A.G.; Di Marco, F.; Gentile, A.; Paggiaro, P.L.; Pegoraro, V.; Pelaia, G.; Rogliani, P.; Santus, P.; et al.
Abstract: Background: The choice of inhaler device for asthma patients depends upon multiple attributes. We investigated factors that may drive general practitioners (GPs) and respiratory specialists in the prescription of inhaler devices for asthma patients who initiated inhalation therapy. Methods: We retrospectively analysed prescriptions by GPs and respiratory specialists to asthma patients commencing inhaled corticosteroid/long-acting β2-agonist combination therapy available as both pressurised metered-dose inhalers (pMDIs) and dry powder inhalers (DPIs). Patient characteristics were compared by device and multivariate analysis was used to model the likelihood of receiving a pMDI as opposed to a DPI in order to identify drivers for prescription. A sample of the respiratory specialists completed an ad-hoc survey of their perceived success in achieving asthma control in their patients and barriers to attaining full control. Results: Prescription of a particular inhaler device was unrelated to the characteristics of the patients. Multivariate analysis revealed that the main driver for the choice of inhaler device was the medication (Odds Ratio and 95% Confidence Interval, respectively for GPs and specialists: 0.19 [0.16–0.23]; 0.17 [0.08–0.37]). Specialists perceived asthma as being inadequately controlled in 41% of their patients, and considered patients' difficulties in using DPIs and pMDIs as instrumental in this, citing a need for a novel, more effective inhaler technology. Conclusion: Physicians choose inhaler devices according to the prescribed drugs and not to the characteristics of the individual patient. This may reflect a lack of confidence in existing inhaler devices and underlines the need for technologies, which are more reliable and easier to use by patients. Highlights: Inhaler choice is as critical as the choice of the medication itself. Prescribers should select the inhaler based on the patient's characteristics and needs. Prescription of a particular inhaler device is unrelated to the characteristics of the patients. The strongest driver of inhaler choice is the medication.